Penerapan Strategi Pemasaran Wisata Kolam Pancing “Cak Rul Fishing” Dalam Perspektif Marketing 4.0 - Arif Zunaidi; Risa Rahmah (Al-Muraqabah: Journal of Management and Sharia Business, 2021)
The world saw a reduction in the phenomenon of environmental effects during this year's Covid19 pandemic. So far, fishing pond tours have already been classified as quiet tour packages because their activities depend on simply sitting around and waiting for fish to become interwoven on the fishing line. Visitors have been few, although most people are aware of its existence, apart from those who share interests. The fishing pond tour "Cak Rul Fishing" was chosen because it had more visitors than other fishing ponds. However, with many advances in technology and existing technological advancements, pond tourism should be able to take advantage of it so that more people are aware of these things. The goal of this research is to become more aggressive in trying to introduce the fishing industry to society. The methodology used in this research is a descriptive method with an analytical-qualitative methodology. While field studies and literature studies are being used to conduct research. According to the research results of his research, in order to improve tourist visits, appropriate information about the existence of fishing pond tourism is deemed necessary, along with attractive promotional programs to attract almost all old and new prospective customers. Policies must be able to give quality details and be easily accessible to the people, and the public must be equipped with sufficient details and praise fishing pond tourism through media platforms.